Simulation of Volcanic Ash Dispersion From Mount Ruang Using the Puff Model (April 29–30, 2024): English - Hidayanti, Arifatul; Hardyanto, Wahyu; Munandar, Arif; Wiujianna, Atri; Meinofelia, Erika (Pusat Penelitian dan Pengembangan BMKG, 2025)
This study aims to simulate and predict volcanic ash dispersion from the 29 April 2024 eruption of Mount Ruang by coupling the PUFF model with RGB analysis of Himawari-8 imagery. Driven by meteorological fields from the NOAA Global Forecast System, the PUFF model provides 24-hour forecasts of ash transport by integrating Lagrangian and Eulerian representations of particle motion. For validation, Himawari-8 satellite imagery was processed using the RGB method with IR1, IR2, and IR4 channels to visually detect the spatial distribution of ash clouds, enabling effective differentiation between volcanic ash and meteorological clouds and improving detection accuracy. The model forecasts closely match the timing and distribution patterns observed in the satellite imagery, indicating strong agreement between numerical simulation and remote sensing analysis. Overall, the results demonstrate that the PUFF model delivers reliable short-term guidance on ash dispersion, and the integration of numerical modeling and satellite-based analysis confirms its effectiveness in supporting early-warning capabilities, aviation safety, and volcanic hazard risk mitigation.